ANALYSIS OF WORKING PERFORMANCE IN ENGINEERING MODIFICATION OF FEROZA VEHICLES WITH FUEL INJECTION SYSTEM - Apriyanto Apriyanto; Mohammad Ma'ruf; Tuharno Tuharno (University of Merdeka Malang, 2019)
Daihatsu Feroza vehicle is one type of official vehicle that is still used to support basic tasks in the ranks of the Army. This vehicle is one of the vehicles that wasteful of fuel. This is influenced by the fuel system used is the conventional fuel system. To overcome this, modifications are made to the fuel system of the feroza service vehicles using a fuel injection system that is more fuel efficient. Testing using the fuel injection system has decreased compared to by using a conventional fuel system at engine power and engine thermal efficiency. From the analysis it was concluded that the effective power and efficiency of the engine produced using the injection system is smaller than using conventional systems. Power at 1800 rpm engine speed uses an injection system that is 210 Nm with a thermal efficiency of 42.97% and uses a conventional system that is 240 Nm with a thermal efficiency of 48.20%.